2007
DOI: 10.1016/j.neuroscience.2007.05.034
|View full text |Cite
|
Sign up to set email alerts
|

The role of transient receptor potential vanilloid 1 in mechanical and chemical visceral hyperalgesia following experimental colitis

Abstract: The transient receptor potential vanilloid 1 receptor (TRPV1) is an important nociceptor involved in neurogenic inflammation. We aimed to examine the role of TRPV1 in experimental colitis and in the development of visceral hypersensitivity to mechanical and chemical stimulation. Male Sprague-Dawley rats received a single dose of trinitrobenzenesulfonic acid (TNBS) in the distal colon. In the preemptive group, rats received the TRPV1 receptor antagonist JYL1421 (10 mumol/kg, i.v.) or vehicle 15 min prior to TNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 60 publications
5
111
3
Order By: Relevance
“…Animal experiments have demonstrated an important role for TRPV1 both in gastro-esophageal (Bielefeldt and Davis, 2008), small intestinal (Rong et al, 2004) and colonic visceral mechanosensitivity as well as in hypersensitivity induced by intracolonic administration of zymosan or neonatal irritation of the colon (Winston et al, 2007). In addition, TRPV1 was shown to be up-regulated in nociceptive visceral afferents of rodents with experimental trinitrobenzene sulfonic acid (TNBS)-induced colitis (Miranda et al, 2007;De Schepper et al, 2008a). De Schepper et al showed that acute TNBS-induced colitis increased the response to colorectal distention in rat pelvic afferent C fibres but not in Ad fibres.…”
Section: Trpv Channelsmentioning
confidence: 99%
“…Animal experiments have demonstrated an important role for TRPV1 both in gastro-esophageal (Bielefeldt and Davis, 2008), small intestinal (Rong et al, 2004) and colonic visceral mechanosensitivity as well as in hypersensitivity induced by intracolonic administration of zymosan or neonatal irritation of the colon (Winston et al, 2007). In addition, TRPV1 was shown to be up-regulated in nociceptive visceral afferents of rodents with experimental trinitrobenzene sulfonic acid (TNBS)-induced colitis (Miranda et al, 2007;De Schepper et al, 2008a). De Schepper et al showed that acute TNBS-induced colitis increased the response to colorectal distention in rat pelvic afferent C fibres but not in Ad fibres.…”
Section: Trpv Channelsmentioning
confidence: 99%
“…TRPV1 knockout (KO) mice exhibit reduced responses of stretch-sensitive afferents (20) and decreased behavioral responses to colorectal distension (CRD) (19) in both naive and hypersensitive states. TRPV1 antagonists similarly decrease afferent and behavioral responses to CRD (9,29,31,52).…”
mentioning
confidence: 93%
“…In a model of colonic hypersensitivity induced by neonatal colonic irritation in rats [81], TRPV1 inhibitors were effective in reducing pain responses to colorectal distension. Increased expression of TRPV1 in DRG is evident in this model, as well as in a TNBS colitis model [82], suggesting that TRPV1 up-regulation may be a mechanism by which the effect of a TRPV1 antagonist becomes manifest. This mechanism was also evident In a model of pancreatic inflammation [83].…”
Section: Changes In Sensory Signalling In Diseasementioning
confidence: 69%
“…This mechanism was also evident In a model of pancreatic inflammation [83]. The up-regulation of function via TRPV1 can be long-term, and may lead to cascades of events resulting in hypersensitivity [81,82]. Alternatively, the translocation of TRPV1 to the cell membrane may have an important influence on its function without changes in mRNA expression [84].…”
Section: Changes In Sensory Signalling In Diseasementioning
confidence: 90%